Building efficient management and leadership practices : the contemporary relevance of Chester I. Barnard's thought in the context of the knowledge-based economy /: the contemporary relevance of Chester I. Barnard's thought in the context of the knowledge-based economy. (2017) - Zanda, Stefania
No abstract available